Discovery Education Transformative Professional Development Model in Egypt: A phenomenological study - Marey, Rezk (AUC Knowledge Fountain, 2020)
This phenomenological study aims to explore teachers’ and principals’ personal experiences with and perspectives on the features of “STEM Now Egypt” program as a transformative professional development (PD) model. It also seeks to examine “STEM Now Egypt” PD program participants’ perceived skills. This study was guided by constructivist principles which were thought to yield transformative PD results. It was conducted in fifteen public schools in Greater Cairo in Egypt and employed a qualitative phenomenological study approach by conducting one to one semi-structured interviews with twelve teachers and three principals selected based on their participation in the two-year “STEM Now Egypt” PD program. All data collected were coded. A thick descriptive representation of findings in almost all participants’ responses was used to find out similar themes and generate conclusions. The research findings reveal general agreement among all participants’ perspectives on PD transformative features, perceived skills, and professional learning pertaining to the literature review and as implemented in “STEM Now Egypt” PD program. All teachers and principals were found to hold positive perspectives toward “STEM Now” extended, and experiential workshops; expert mentoring for follow-up support; principals’ participation in the PD program side by side with teachers; embedding technology in content-based and contextualized training; coherence in addressing digital curricula, research-based instructional strategies and ways of assessing 21st century skills; face-to-face and online professional learning communities; and ongoing feedback and reflection. The study also generated some recommendations that might transform future PD programs in Egypt.